Alkyl-promoted iridium complex for high-performance deep-red phosphorescent organic light-emitting diodes. (August 2022) - Bi, Yan; Chen, Shanyong; Zhao, He; Zhang, Xiyan
Abstract: In this work, a novel deep-red (642 nm) iridium complex, Ir(bp4b)2 (dend), is developed. The introduction of alkyl groups in ligands weakens the intermolecular interactions and endows Ir(bp4b)2 (dend) with favorable physical properties: short photoluminescence lifetime (271.6 ns), low concentration sensitivity (10 −6 to 10 −4  M) and balanced charge-transporting ability. Ir(bp4b)2 (dend)-doped phosphorescent device displays high efficiencies (9.62 cd/A, 12.25 lm/W, 15.29%), low roll-off of efficiencies (from 10 to 1000 cd/m 2 : no decrease; from 1000 to 5000 cd/m 2 : 10.6%), relatively low concentration sensitivity (from 5% to 15%), long device lifetime ( T 80 : 5225 h at 100 cd/m 2 ) and very stable electroluminescent spectra (from 1 cd/m 2 to maximum luminance). This performance is comparable to those of previous record deep-red (around 640 nm) phosphorescent emitters. More importantly, compared with previous record emitters, Ir(bp4b)2 (dend) reports more kinds of excellent parameters and such comprehensive deep-red emitter is rare at present. Graphical abstract: Image 1 Highlights: A novel deep-red (642 nm) iridium complex with favorable physical properties is developed. Ir(bp4b)2 (dend)-doped phosphorescent device displays high and comprehensive performance. This device performance is comparable to those of previous record deep-red (around 640 nm) phosphorescent emitters.